Key Drivers of Digital Transformation among MSMEs in Kulon Progo Regency - Yantoro, Yuli; Ma'ruf, Ahmad; Tri Basuki, Agus (JURNAL MANAJEMEN MOTIVASI, 2026)
Digital transformation remains context-specific for MSMEs, especially in non-metropolitan regions. This study examines its drivers among MSMEs in Kulon Progo Regency, Indonesia, using an exploratory qualitative design and MICMAC analysis of expert judgments from practitioners, academics, and government. Twenty variables were mapped through influence–dependence analysis. Results indicate that external forces customer digital demand, competitive pressure, digital infrastructure, ecosystem conditions, and cybersecurity concerns are primary drivers. Organizational and institutional factors function mainly as relays, while internal capabilities appear as outcomes. The findings highlight policy priorities to strengthen external enablers and intermediary mechanisms for sustainable regional MSME digitalization.